Conditions of work, labor stress, university dependence and psychological well-being in university professor - A. Millán; N. Calvanese; M. E. D'Aubeterre (Universitat Politècnica de València, 2017)
In this study, we proposed to identify the effect of the university dependence (official or private), the perception of sources of work stress, the assessment of working conditions and the psychological wellbeing, by comparing degree of adjustment Of two models differentiated according to the order of the causal influence of the mediating variables. For this, we applied the Psychological Well-Being Scale (Sánchez-Canovas, 2007), the Survey on Working Conditions (Blanch et al., 2010) and the Inventory of perception stressors for University Teachers (Alvarez et al., 2011), in 903 teachers, thouse worked into 32 universities in Venezuela. A path analysis has been carried out which revealed 42 significant causal relationships on psychological well-being, where it is evident that they work in an official university, increase the perception of work stress In the negative evaluation of certain working conditions and with negative impact on Psychological wellbeing. It is also highlighted in the results obtained that the teachers' concern for the academic level of the students, dampens the negative impact on the welfare. The main contribution of this work was to clarify the effect that certain variables of the university organization have as risk factors for the psychological well-being of university teachers, which could help design or prioritize specific intervention strategies for each kind of university.